Unraveling the Nexus of Science & Technology Input and Economic Growth through Research & Development (R&D) Indicators in Asia-pacific Region: A Panel Data and Causality Analysis - Emmanuel Onsay (Camarines Sur Polytechnic Colleges, 2021)
This paper unravels the critical aspect of science and technology through research and development indicators as sources, drivers, and predictors of economic growth from the perspective of two developing countries, namely: Philippines and Thailand (ASEAN), and two developed economies, namely: Japan and Australia (ASEAN-X) in Asia-Pacific Region. The data set ranges from 1980 to 2019 and is collected from World Development Indicators of the World Bank, Institute for Statistics of United Nations Educational, Scientific and Cultural Organization (UNESCO), and World Intellectual Property Organization (WIPO). Research and Development (R&D) is a tool for generating new knowledge and serves as input for technological advancement. In the long run, it has been proven that technology can sustain permanent economic development in the economy. In developed economies, the nexus between the aforementioned variables is robust and significant. Thus, the R&D indicators can be used as a predictor of economic growth. However, in developing economies, the nexus of variables involved is negligible and insignificant. Hence, the R&D indicators cannot be effectively utilized as a predictor of economic growth. Furthermore, the study combined the two sets of panel data and a relevant conclusion was drawn. A country-panel regression and causality analysis were performed based on the empirics of macroeconomics.